Pictures from a Drawer : Prison and the Art of Portraiture - Jackson, Bruce, 1936- (Book collections on Project MUSE., 2009)
For more than forty years Bruce Jackson has been documenting-in books, photographs, audio recording, and film-inmates' lives in American prisons. In November, 1975, he acquired a collection of old ID photos while he was visiting the Cummins Unit, a state prison farm in Arkansas. They are published together for the first time in this remarkable book. The 121 images that appear here were likely taken between 1915 and 1940. As Jackson describes in an absorbing introduction, the function of these photos was not portraiture-their function was to "fold a person into the control.